Contributions of Loading and Unloading to Overpressure: Analytical Results from The Shelfal Area of The Lower Kutai Basin, Indonesia - Ramdhan, Agus M.; Hutasoit, Lambok M. (Geological Agency, 2022)
A modified Bowers Method is applied to analyze the contribution of loading and unloading to total overpressure magnitude in the shelfal area of the Lower Kutai Basin. The method combines Bowers Method with density-sonic cross plots to differentiate contributors to overpressure. This method has a strong physical background, and has proven to give satisfactory overpressure estimation in the studied area. Several processes related to overpressure and compaction in the studied area have also been deduced: 1) top of overpressure is caused by unloading due to gas generation, 2) gas generation on its own can produce overburden-scale overpressure magnitude, 3) loading starts to contribute to overpressure at depth, where the lithology is dominated by mudrocks, 4) effective stress history experienced by mudrocks before unloading, and 5) the presence of two compaction lines and therefore two associated velocity-effective stress relations.